2012
DOI: 10.1080/00268976.2012.681311
|View full text |Cite|
|
Sign up to set email alerts
|

Computationally efficient molecular dynamics integrators with improved sampling accuracy

Abstract: The design of numerical integrators for particle simulations with arbitrary potentials entails fundamental tradeoffs between the accuracy achieved and the amount of computation required. Here we introduce a class of explicit variational integrators designed to achieve high accuracy for quadratic potentials, with little additional computation relative to traditional integrators. We show that, in practice, these new integrators also improve accuracy for classical biomolecular simulations, since the potential in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Advancements in massively parallel computing, including new algorithms 42 and hardware, 20 promise sustained progress in carbohydrate modeling. Our findings (e.g., Table 1) are consistent with previous reports, which have concluded that extending carbohydrate simulations to μs timescales is essential to explain experimental observations 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Advancements in massively parallel computing, including new algorithms 42 and hardware, 20 promise sustained progress in carbohydrate modeling. Our findings (e.g., Table 1) are consistent with previous reports, which have concluded that extending carbohydrate simulations to μs timescales is essential to explain experimental observations 43 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the efficiency of the proposed AIA scheme, we compared it in accuracy and performance with the velocity Verlet integrator and with the two-stage integrator (BCSS) of Blanes et al [1]. In addition, some selected tests also involved the two-stage HOH scheme by Predescu et al [27]. All tests probing various integrating schemes have been repeated with three different simulation techniques, MD, HMC and GHMC.…”
Section: Numerical Experiments 41 Testing Proceduresmentioning
confidence: 99%
“…Section 5 is devoted to numerical results. The performance of the AIA method is compared with the standard velocity Verlet algorithm and the two-stage integrators with the fixed parameter values suggested in [1] and [27]. In all experiments and for each of the criteria employed, the performance of AIA is at least as good as, and often significantly better than, the performances of the Verlet scheme and the fixed parameter two-stage integrators.…”
Section: Introductionmentioning
confidence: 99%
“…On the theoretical and computational side, the special issue entitled 'Quantum Molecular Dynamics', in honour of Prof. William H. Miller (numbers 9, 10 of vol. 110, in 2012) contains a rich variety of articles on all aspects of chemical dynamics, including a perspective by Nobel Laureate Rudolph A. Marcus [11], and articles on defining the hydrogen bond [12], improved integrators for classical molecular dynamics [13], and improvements to ring polymer molecular dynamics for calculating reaction rates [14]. Mixing theory and experiment, the Festschrift for Nobel Laureate Dudley R. Herschbach (numbers 15, 16 of vol.…”
Section: Editorialmentioning
confidence: 99%